Changes in detrital input, ventilation and productivity in the central Okhotsk Sea during the marine isotope stage 5e, penultimate interglacial period. (1st May 2018) - Jimenez-Espejo, Francisco J.; García-Alix, Antonio; Harada, Naomi; Bahr, André; Sakai, Saburo; Iijima, Koichi; Chang, Qing; Sato, Keiko; Suzuki, Katsuhiko; Ohkouchi, Naohiko
Graphical abstract: Highlights: Three different periods can be distinguished during the Marine Isotope Stage 5e mainly based on marine productivity changes. During Termination II, an offset between surface productivity and bottom ocean changes (δ 18 O benthic) occurs. Eu ∗ values indicate an input from the Kurile Islands during late MIS 5e. Certain aeolian input variations are not synchronous to water column changes. Abstract: By presenting benthic foraminifera isotope profiles and bulk geochemical composition of core sediments, we offer a mutiproxy reconstruction of the central Okhotsk Sea oceanography between ∼130 to and ∼115 kyr, related to the marine isotopic stage 5e (MIS 5e). Sediments from the site MR0604-PC7A have been compared with paleo- sea surface temperatures and other records. This multiparameter approach allowed to recognize three periods for MIS 5e evolution, characterized by variations in marine productivity and bottom oxygenation. These variations have been ultimately associated with the production of Okhotsk Sea Intermediate Water and the presence or absence of nutrient contribution from the Pacific Deep Water into central Okhotsk Sea. Aeolian input reconstructed by Th/Sc ratio indicates higher values during the MIS 6 and MIS 5d compared with the MIS 5e. Eu ∗ values indicate an input of detrital material from Kurile Islands and East-Kamchatka during the late MIS 5e, absent during the early MIS 5e and glacial periods.